Analisis Sistem Pengendalian Internal dalam Upaya Meningkatkan Daya Saing pada Toko Sembako - Rizkison Rizkison; Robiatul Adawiyah; Rio Eldianson (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The development of the globalization era economy in Indonesia today has encouraged very tight competition in the business world. Challenges in business competition do not only come from within the country but have also been visited by competitors from abroad with products that have high competitive quality. If the company does not have a good internal control system, the company will automatically be eliminated, so that it will also have an impact on social economic growth. The purpose of this study is to determine and analyze the Internal Control System in an Effort to Increase Competitiveness at the Tegalsawah Village Grocery Store, East Karawang District. The type of research used is qualitative, with methods in the form of Interviews, Observations and documentation. The data analysis model used is the descriptive analysis method, which is an analysis technique by collecting, classifying, managing, describing data that is relevant to the problem being studied so as to make conclusions. The results of this study indicate that, in the efforts that can be made by grocery store business owners to manage their business optimally, one of them is implementing controlled internal control. The basis for this grocery store owner is to create balance and suitability to achieve effectiveness and efficiency in order to achieve profit.